The tablets and their scribes (Wiesbaden)
xxxi, 380 sayfa
Keywords: “In May 2024, the ”Corpus der hethitischen Festrituale (HFR)” project organized its second International symposium and brought together distinguished scholars from various countries to discuss a range of phenomena pertaining to scribal habits and practices in Hittite Anatolia during the second millennium BCE. The symposium addressed both the methods of digital and traditional approaches to understand ancient writing practices and scribal customs. After a comprehensive introduction, the alphabetically arranged contributions explore various topics by different authors, e.g. stylometric approaches, digital palaeography and the origins of Hittite scribal practices. Furthermore, it comprises the research on palaeographic features in texts from regions outside the Hittite capital Ḫattuša (texts from Maşat Höyük, from Kayalıpınar and from Büklükale). The majority of the contributions focus on specific corpora of Hittite texts and analyze their palaeography or investigate the number of scribes involved. These texts include administrative records, cult inventories, the ḫišuwa festival, Palaic texts, the nuntarriyašḫa festival, Hittite votive inscriptions, the Zukraši text, the AN.DAḪ.ŠUM festival, and Hittite divination texts. With this volume, the HFR project offers a study that not only presents the current state of Hittite palaeography, but also establishes a foundation for future research, particularly that involving automated analytical tools“ --